Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1037/a0035454
|View full text |Cite
|
Sign up to set email alerts
|

Can college students use emotion regulation strategies to alter intimate partner aggression-risk behaviors? An examination using I³ theory.

Abstract: Objective: Drawing on Finkel and Eckhardt’s I3 theory (Finkel & Eckhardt, 2013), this experimental study examined the effects of emotion regulatory efforts on aggressive verbalizations during anger arousal. Methods: Participants were 236 male and female college students with and without a history of intimate partner aggression (IPA) perpetration. Participants were randomized to 1 of 3 emotion regulation strategy conditions: cognitive reappraisal, expressive suppression, or no instruction. They were trained to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 64 publications
5
54
1
Order By: Relevance
“…Specific changes in anger were also examined by producing an anger summary score with the five adjectives "angry," "hostile," "irritable," "disgusted," and "annoyed." This is consistent with past research examining IPA Eckhardt, Jamison, & Watts, 2002;Maldonado, DiLillo, & Hoffman, 2014). These adjectives have been shown to form a distinguishable anger factor when negative mood adjectives are factor analyzed (e.g., Watson & Clark, 1992).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Specific changes in anger were also examined by producing an anger summary score with the five adjectives "angry," "hostile," "irritable," "disgusted," and "annoyed." This is consistent with past research examining IPA Eckhardt, Jamison, & Watts, 2002;Maldonado, DiLillo, & Hoffman, 2014). These adjectives have been shown to form a distinguishable anger factor when negative mood adjectives are factor analyzed (e.g., Watson & Clark, 1992).…”
supporting
confidence: 78%
“…However, prior research examining rates of IPA over six months among university students has found much higher rates than found here (e.g., 50.7% to 58.9% and 28.8%; Watkins, Maldonado, & DiLillo, in press;Maldonado et al, 2014). It seems likely that the comparatively low rates found here are due to the extensive exclusion criteria of the current study.…”
Section: Descriptive and Manipulation Check Findingscontrasting
confidence: 54%
See 1 more Smart Citation
“…Techniques for neurocognitive LP assessment are not limited to the CVLT-II and WCST (Boosman et al, 2014), and it may be possible to develop dynamic assessments in other domains to predict different types of skill acquisition. For example, existing brief intervention-like emotion regulation techniques could be adapted for use as dynamic assessments (Maldonado et al, 2015; Scott et al, 2015; Watkins et al, 2015). Further, proof-of-concept single-session social cognitive training techniques could provide dynamic assessment of theory of mind (Kayser et al, 2006; Sarfati et al, 2000), affect recognition (Combs et al, 2008; Penn & Combs, 2000; Russell et al, 2008; Silver et al, 2004), and social perception (Corrigan & Toomey, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the harm caused to the victim, IPV results in billions of dollars per year of medical expenses in addition to loss of productivity in the workforce (Karakurt, 2013;Maldonado, DiLillo, & Hoffman, 2015;White & Satyen, 2015;Messings, Thaller, & Bagwell, 2014). Violence that occurs in romantic relationships is extremely evident and rising incidences have garnered much attention, specifically on college campuses (Capezza, Schumacher, & Brady, 2014;Reed, Hines, Armstrong, & Cameron, 2015).…”
Section: Introductionmentioning
confidence: 99%